2008
DOI: 10.2514/1.17720
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Investigation of Chevron Nozzle Mechanisms

Abstract: A detailed investigation into the effect of chevron nozzles on the near-field acoustics of a separate flow exhaust system was conducted at the University of Cincinnati Anechoic Test Facility. Chevrons with varying numbers of lobes and levels of penetration were selected to provide insight into the effects of these geometric parameters on the acoustic near field. Tests were conducted at two different nozzle operating conditions and the chevrons were shown to produce substantial modifications to the near field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…In attempts to shed further light on the low-and high-frequency jet noise generation, a series of studies on coaxial jets and different modifications of chevron nozzles at the core jet were conducted by Callender et al [11][12][13]. In their first investigation, chevron nozzles were observed to be more effective at lower acoustic frequencies and aft directivity angles.…”
Section: Circular Coaxial Modified Nozzle Jetsmentioning
confidence: 97%
“…In attempts to shed further light on the low-and high-frequency jet noise generation, a series of studies on coaxial jets and different modifications of chevron nozzles at the core jet were conducted by Callender et al [11][12][13]. In their first investigation, chevron nozzles were observed to be more effective at lower acoustic frequencies and aft directivity angles.…”
Section: Circular Coaxial Modified Nozzle Jetsmentioning
confidence: 97%
“…Chevroned nozzle lips [1,2], nozzle-exit plasma actuators [3,4], fluidic actuators [5], and many other techniques are currently being explored for this objective. Seemingly without exception, a significant degree of parametric exploration is employed in these efforts.…”
Section: Introductionmentioning
confidence: 99%
“…In subsonic jets, properly designed chevron nozzles produce lower overall acoustic radiation levels than those of a corresponding round nozzle 6,7,8,9 . Experiments have shown that increasing chevron penetration decreases low frequency noise and often increases high frequency noise (sometimes referred to as high frequency crossover).…”
Section: Introductionmentioning
confidence: 99%